Enzyme-free direct detection of histamine in peanuts using novel γ-MnOOH-W3O10 nanostructure-modified electrode. (23rd January 2023) - Kushwaha, Amisha; Singh, Gajendar; Gaur, Umesh Kumar; Sharma, Manu
Abstract : Direct electrochemical detection of histamine (HS) in peanuts was carried out using MW@GCE. MW (MnO4 W) was prepared by the hydrothermal treatment of γ-MnOOH and W3 O10 nanostructures. Abstract : Direct electrochemical detection of histamine (HS) in peanuts was carried out using MW@GCE. MW (MnO4 W) was prepared by the hydrothermal treatment of γ-MnOOH and W3 O10 nanostructures. The synthesized γ-MnOOH (MNO), W3 O10 (WO), and MnO4 W (MW) nanostructures were characterized using XRD, FE-SEM, HR-TEM, XPS, and SECM techniques for structural, morphological, and electrochemical properties. MW@GCE was the superior electrode in comparison with MNO@GCE and WO@GCE, as confirmed by CV, Mott-Schottky, and impedance analyses. The limit of detection for the MW@GCE sensor was recorded as 5.817 nM and 3.7 nM from DPV and amperometric analyses, respectively. HS sensitivity was also recorded as 233.99 μA μM −1 cm −2 and 664.20 μA μM −1 cm −2 from DPV (0.1–0.16 μM) and amperometric analyses, respectively. Furthermore, HS detection in the peanut extract was done, and ∼0.16 μM (average amount) HS was quantified based on 18 concentrations. The usual spiking approach was also used for HS validation in peanuts with recoveries ranging from 105.3 to 106.2% and relative standard deviations ranging from 2.41 to 3.19%. The MW@GCE electrode's robustness was explored in terms of long-term storage, repeatability, and reproducibility Because of the direct detection capabilities of HS in peanuts and its resilience, this sensing system is useful for food and pharmaceutical sample analysis.